Prognostic value of secondary hyperaldosteronism in patients with chronic heart failure with preserved ejection fraction - A. N. Shevelok (Медицинский вестник Юга России, 2021)
Purpose: to investigate the prognostic value of secondary hyperaldosteronism patients with heart failure with preserved ejection fraction. Materials and methods: prospective cohort study included 158 patients with hyperaldosteronism and heart failure with preserved ejection fraction. Baseline blood aldosterone levels were determined in all patients. Hyperaldosteronemia was diagnosed when the plasma aldosterone level was > 160 pg/ml. The primary endpoint was all-cause mortality. Results: at baseline, hyperaldosteronemia was detected in 59 of 158 patients (37.3%). Hyperaldosteronemic patients were younger, had higher functional class and NT-proBNP level, and a higher rate of comorbidity (all Ps <0.05). Over a median follow‐up of 32 (28-38) months, a total of 50 (37.6%) patients died. Cardiovascular death occurred in 32 (20.3%) cases, non-cardiovascular – in 18 (11.4%) cases. A total of 65 (41.1%) patients were hospitalized for HF. High aldosterone levels were associated with a significant (p <0.05) increase in the risk of hospitalization for HF (adjusted odds ratio (OR) 2.14, 95% confidence interval (CI) 1.34-9.68), all-cause death (OR 1.64; 95% CI 1.23-7.65, P = 0.033) and HF death (OR 1.56; 95 % CI 1.14-11.3, P = 0.021). Conclusion: Hyperaldosteronism in patients with heart failure with preserved ejection fraction secondary hyperaldosteronism is an independent predictor of hospitalization for heart failure, all-cause, and cardiovascular mortality. The inclusion of plasma aldosterone level in the existing prognosis models of heart failure with preserved ejection fraction will help improve their predictive value and optimize the management of high-risk patients.